Utilising fuzzy interpolation Bezier curves for alphabet verification - Rozaimi Zakaria; Soon, Yun Yee (Universiti Malaysia Sabah, 2019)
In this paper, alphabet verification is conducted using fuzzy interpolation Bezier curves. Uncertain data can be defined by using the fuzzy number concept. Firstly, Fuzzification in the form of triangular fuzzy numbers is discussed. Then, the defuzzification process is implemented to produce crisp fuzzy data points. An error is obtained by comparing the defuzzified model of alphabet verification with the crisp model. The small error value obtained indicates that the fuzzy interpolation Bezier curve model is acceptable and can be used in modeling alphabet verification.